2021
DOI: 10.1016/j.medj.2021.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Cell-free DNA tissues of origin by methylation profiling reveals significant cell, tissue, and organ-specific injury related to COVID-19 severity

Abstract: COVID-19 affects the entire body. Cheng et al. describe a DNA-based blood test to quantify cell and tissue injury due to COVID-19. They show that severe COVID-19 is associated with increased lung, liver, and erythroblast DNA in blood and that the concentration of cell-free DNA correlates with disease progression.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
68
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 58 publications
4
68
0
3
Order By: Relevance
“…Tissue-specific cfDNA markers correlated with known biochemical measures of end-organ injury. Some of these tissue-specific cfDNA markers demonstrated high performance to identify patients who required ICU care or who subsequently died, similar to the findings of a recent report ( 37 ). After multivariate analysis correcting for known risk factors for severe COVID-19 disease, including increasing age, male sex, and obesity, there remained a significant association of elevated risk of poor clinical outcome.…”
Section: Discussionsupporting
confidence: 85%
“…Tissue-specific cfDNA markers correlated with known biochemical measures of end-organ injury. Some of these tissue-specific cfDNA markers demonstrated high performance to identify patients who required ICU care or who subsequently died, similar to the findings of a recent report ( 37 ). After multivariate analysis correcting for known risk factors for severe COVID-19 disease, including increasing age, male sex, and obesity, there remained a significant association of elevated risk of poor clinical outcome.…”
Section: Discussionsupporting
confidence: 85%
“…In contrast to other infectious diseases that also induce autoantibodies ( Rivera-Correa & Rodriguez, 2018 ), we observed that the levels of IC are not increased in the circulation of COVID-19 patients. This is unexpected, considering the high levels of autoimmune antibodies with specificities for antigens that are likely to be accessible in the circulation, such as PS in exosomes or cell-free DNA ( Cheng et al, 2021 ). However, it is possible that IC are being formed, but are rapidly removed from the circulation, which would be consistent with the observed correlations between levels of IC and parameters indicating kidney disfunction.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 patients have high levels of cell-free DNA in the circulation, which are also related to disease severity ( Lee et al, 2020 ; Cheng et al, 2021 ). Furthermore, we observed a strong correlation between markers of cell injury and anti-DNA levels, which mirrors the previously found correlation between these markers and cell-free DNA levels ( Cheng et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MN may also contribute to cfDNA when they are extruded from live cells as has been shown in live cell imaging studies in vitro but this has yet to be demonstrated in vivo [ 38 , 39 ]. Recent investigations showed that severity of COVID-19 disease and its progression is significantly associated with cfDNA in plasma, especially cfDNA identified as originating from lung, liver and erythroblasts identified using DNA methylation profiling [ 40 , 41 ]. Some of the cfDNA originates from neutrophil extracellular traps (NETs) that are released by neutrophils to destroy pathogens; it was reported that sera from patients with COVID-19 have elevated levels of myeloperoxidase-DNA complexes, and citrullinated histone H3 that are specific biomarkers of NETs [ 42 ].…”
Section: The Cellular Responses To Viral Infections and Covid-19 In Particularmentioning
confidence: 99%